Evaluation of the new (USDA, 1974) carcass beef quality grade standards - D.R. Campion; J.D. Crouse; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 1976)
Carcasses from 1,117 steers from Hereford and Angus dams mated artificially to Hereford, Angus, Charolais, Jersey, South Devon, Simmental and Limousin sires were studied. The study was to evaluate the UDSA 1965 quality grade ('65-QG) standards in relation to palatability of rib steaks, and also to see how the new grades change the distribution of carcasses in each grade. Rib steaks from 494 of these carcasses were cooked and evaluated by a taste panel; a rib steak from each of the 1,117 carcasses was cooked and measured for tenderness by a Warner-Bratzler shear-device. All data were adjusted to a constant carcass weight of 626 lb.
Keywords: Cattlemen' s Day; 1976; Report of progress (Kansas State University. Agricultural Experiment Station); 262; Beef; Carcass quality; Tenderness; Palatability